In vitro and in silico investigation of the plant growth-promoting rhizobacteria from pepper (Piper nigrum L.) - Ab. Aziz, Zakry Fitri (2013)
The increase in awareness of the public to use inexpensive, safe, organic and environmentally friendly agricultural inputs makes plant growth-promoting rhizobacteria as one of the more attractive biological applications used to reduce or complement the use of synthetic agricultural inputs. In the present study, diligent investigation has been conducted in search of the most promising plant growthpromoting rhizobacteria from pepper (Piper nigrum L.) rhizosphere. As a result of the search, 14 rhizobacteria were isolated from the rhizosphere of the pepper plant (Piper nigrum L.). In vitro analyses showed that the isolates possessed many traits beneficial to agronomy, viz. biological nitrogen fixation, phosphate solubilisation and indole acetic acid (IAA) production. Analyses by 16S rRNA sequencing indicated that the isolates belonged to Acinetobacter radioresistens (UPMLH19), Bacillus cereus (UPMLH1, UPMLH13, UPMLH24, UPMLH41 and UPMLH42), Bacillus megaterium (UPMLH3 and UPMLH22), Bacillus subtilis (UPMLH5), Bacillus spp. (UPMLH8, UPMLH23, UPMLH34 and UPMLH43) and Leclercia sp. (UPMLH2). Phylogenetic analyses indicated that the newly isolated rhizobacteria from P. nigrum were from Firmicutes and Proteobacteria, with the former being more common. In the present study, computational methods were used to predict information within the small subunit 16S rRNA gene from B. cereus strain UPMLH24. The computational methods employed revealed that the small subunit 16S rRNA gene sequence from B.cereus strain UPMLH24 contained several open reading frames that encoded gamma-polyglutamic acid protein, lipoprotein, cytoplasmic protein and ribosomal protein S10. Computational predictions based on protein-protein identity classified seven phyla of organisms associated with small open reading frames of novel B.cereus strain UPMLH24. Plant bioassay technique was used to select the most promising isolates. Three vegetable crop species were used as test plants, namely mustard (Brassica juncea), mung bean (Vigna radiata) and shallot (Allium scalinocum). Of the 14 inocula, Bacillus spp. strains (UPML23, UPMLH34 and UPMLH43) and B. cereus UPMLH24 improved early plant growth of mustard significantly. Early development of mung bean seedlings showed significant improvement after inoculation with Bacillus sp. strain UPMLH8, B. megaterium strains UPMLH3 and UPMLH22, and B. cereus strain UPMLH24. Only B. cereus strain UPMLH1, significantly promoted root number and shoot height of shallot plants. B. cereus strains UPMLH1 and UPMLH24 inoculum were selected and used in further investigation after showing to be the most promising in enhancing the early development of mustard, bean and shallot plants. The selected strains of B. cereus were then used to evaluate the effect of inoculation on their original host, P. nigrum stem cuttings of Kuching variety, studied for root formation under nursery conditions. Results showed that B. cereus UPMLH24 inoculation on fresh pepper stem cuttings stimulated root number (55% increase over control), length of longest root (25% increase over control), total root length (87% increase over control), root fresh weight (28% increase over control) and root dry weight (112% increase over control). Present study recommends Bacillus cereus UPMLH24 as a potential candidate in a formulation of a biostimulant for organic and sustainable nursery for pepper production.